High Dielectric, Robust Composite Protective Layer for Dendrite‐Free and LiPF6 Degradation‐Free Lithium Metal Anode. (9th September 2019) - Jang, Eun Kwang; Ahn, Jinhyeok; Yoon, Sukeun; Cho, Kuk Young
Abstract: The development of lithium metal anodes for next generation batteries remains a challenge. Uncontrolled Li dendrite growth not only induces severe safety issues but also leads to capacity fading by continuously consuming the electrolyte. This study demonstrates the design and fabrication of a composite protective layer composed of a high dielectric polymer, inorganic particles, and an electrolyte to overcome these obstacles. This layer not only suppresses dendrite growth, but also prevents LiPF6 degradation. The electrolyte introduced in the protective layer remains within the coating layer after solvent removal and acts as an ion transport channel at the interface. This enables the protective layer to exhibit high ionic conductivity and mechanical strength. The composite protective layer, which exhibits synergistic soft‐rigid characteristics, is placed on the Li metal anode and facilitates superior interfacial stability during long‐term cycles. LiMn2 O4 /coated lithium full cells using the composite protective layer show a superior rate capability and enhanced capacity retention compared to the cells using a bare lithium anode. The proposed strategy opens new avenues to fabricate a sustainable composite protective layer that affords superior performance in lithium metal batteries. Abstract : A high dielectric constant organic–inorganic composite protective layer that prevents salt degradation as well as dendrite formation is fabricated onto the lithium metal anode. Introduction of the electrolyte in the coating solution provides a seamless ion transport channel and exhibits high ionic conductivity and transport number with a synergistic effect of using high dielectric constant inorganic and organic component.